2011
DOI: 10.1021/np100701s
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activity of Benzoyl Ester Clerodane Diterpenoid Derivatives from Dodonaea polyandra

Abstract: Four new benzoyl ester clerodane diterpenoids, 15,16-epoxy-8α-(benzoyloxy)methylcleroda-3,13(16),14-trien-18-oic acid (1), 15,16-epoxy-8α-(benzoyloxy)methyl-2α-hydroxycleroda-3,13(16),14-trien-18-oic acid (2), 15,16-epoxy-8α-(benzoyloxy)methyl-2-oxocleroda-3,13(16),14-trien-18-oic acid (3), and 15,16-epoxy-2α-benzoyloxycleroda-3,13(16),14-trien-18-oic acid (4), have been isolated from the leaves and stems of Dodonaea polyandra. The anti-inflammatory activities of compounds 1, 2, and 4 were evaluated by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…This species grows within a localized region of tropical Cape York Peninsula, Queensland. The findings demonstrated that a male individual of D. polyandra consisted of labdane diterpenoids as major constituents [23] in contrast to the female which possessed clerodane diterpenoids [24]. A more commonly researched and related species, Dodonae aviscosa (Sapindaceae), is also dioecious (along with many other species in this genus), however there has been no distinction made between the phytochemistry of male and female plants.…”
Section: Effect On Secondary Metabolite Productionmentioning
confidence: 99%
“…This species grows within a localized region of tropical Cape York Peninsula, Queensland. The findings demonstrated that a male individual of D. polyandra consisted of labdane diterpenoids as major constituents [23] in contrast to the female which possessed clerodane diterpenoids [24]. A more commonly researched and related species, Dodonae aviscosa (Sapindaceae), is also dioecious (along with many other species in this genus), however there has been no distinction made between the phytochemistry of male and female plants.…”
Section: Effect On Secondary Metabolite Productionmentioning
confidence: 99%
“…1). Each of the isolated compounds possesses a labdane skeleton, which is in contrast to the clerodane diterpenoids reported recently from the same plant species (Simpson et al, 2011a). The following paragraphs report the structural elucidation of the new compounds isolated.…”
Section: Resultsmentioning
confidence: 86%
“…However, diterpenoids previously isolated from D. polyandra have all contained a clerodane skeleton (Simpson et al, 2011a). Labdane and clerodane classes are biosynthetically related via a series of methyl and hydride shifts (George et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The bioactivity was concentrated to within a small number of subfractions obtained from chromatographic separation processes of the extract. Eventually, four benzoyl ester furanoclerodane diterpenoids were isolated, of which three were established as contributing a major part of the anti-inflammatory effects of the plant (47).…”
Section: Kuuku I'yu Medicinal Plant Projectmentioning
confidence: 99%